SERAPAN P DAN HASIL TANAMAN KEDELAI (Glycine Max (L) Merr.) AKIBAT PENINGKATAN DOSIS PUPUK HAYATI VP3 DAN LAMA INDUKSI LISTRIK - achmad sidiq syafi'i; Sugiarto Sugiarto; Novi Arafita (AGRONISMA, 2021)
This study aims was to determine the effect of increasing the dose of VP3 biofertilizer and the duration of electrical induction on P absorption on soybean crop and on soybean crop yields. The research was conducted in the experimental field of Griya Shanta, Brawijaya University, Malang and Microbiology Laboratory, Islamic University of Malang. The design used was a simple randomized block design (RAK) with 13 treatments which were repeated 3 times. P uptake was calculated from all parts of the soybean plant. The results showed that the application of VP3 biofertilizer with a certain electrical induction duration could increase P absorption which was shown in the best treatment V12 (VP3 200% + Electric Induction 90 minutes) by 2124.5 ppm but not significantly different from V10(NPK 100% + Electric Induction 90 minutes), V2(VP3 100%) and V3(VP3 200%). Meanwhile, the yield of soybean plants treated with V2L1 (Biofertilizer VP3 200% + 30 minutes electrical induction) with a productivity of 5.46 Ton/ha (tons per hectare).